Automatic inverted pendulum control system - Mohd Syazwi Helmi, Jashari (2013)
This project is about developing of an Inverted Pendulum that been control by PID controller. The Inverted Pendulum is a classical control system problem due its nonlinear characteristic and unstable behavior. It is have same concept like the hand (broom) to maintain the stick upright. An inverted pendulum is a pendulum attach directly with the sensor (potentiometer) at pivot point. The cart mounted directly on the tire to move horizontal either forward or backward. The movement of mechanical part can be determining using PID controller and implement to microcontroller.Microcontroller used in this project is Arduino UNO. PID controller is obtained using MATLAB through Simulink. Lastly, the performances of PID controller are test on hardware to maintain the pendulum upright. Based on the result, the inverted pendulum manages to reach stability.